1994
DOI: 10.1002/jez.1402690109
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the lysosomal system in yolk protein deposit and degradation during vitellogenesis and embryonic development in trout

Abstract: In adult female rainbow trout (Oncorhynchus mykiss), an immunocytochemical study of the oocyte has shown that a proteolytic enzyme, cathepsin D, is localized in multivesicular bodies (MVB) which begin to differentiate before the phase of vitellogenesis. Estrogens cause the liver to synthesize the protein vitellogenin (VTG), which then enters the systemic circulation. During vitellogenesis, endocytosed VTG is co-localized with cathepsin D in the MVB.Assays of oocyte cathepsin activities have shown that the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 34 publications
4
74
1
Order By: Relevance
“…After leaving the blood vessels, vtg goes through the follicle wall and is selectively incorporated into the oocyte [105], by receptor-mediated endocytosis [106,107]. Vtg is then transferred into multivesicular bodies from the lysosomial compartment [108] where it is colocalised with a proteolytic enzyme, cathepsin D [109], which is probably responsible for its cleavage into yolk proteins.…”
Section: Vitellogenesismentioning
confidence: 99%
“…After leaving the blood vessels, vtg goes through the follicle wall and is selectively incorporated into the oocyte [105], by receptor-mediated endocytosis [106,107]. Vtg is then transferred into multivesicular bodies from the lysosomial compartment [108] where it is colocalised with a proteolytic enzyme, cathepsin D [109], which is probably responsible for its cleavage into yolk proteins.…”
Section: Vitellogenesismentioning
confidence: 99%
“…In the past decade, many attempts have been undertaken on the biochemical composition of egg yolk components and their digestion, synthesis and transformation during embryonic development of teleosts (Henderson and Tocher 1987;Heming and Buddington 1988;Rønnestad and Fyhn 1993;Wiegand 1996;Poupard et al 2000). A large amount of data revealed that the formation of a YSL (yolk syncytial layer), a structure unique to teleosts, enables the resorption of the yolk reserves and development to the larval stage (Manfredi Romanini et al 1969;Walzer and Schönenberger 1979a;Shimizu and Yamada 1980;Cousin et al 1987;Sire et al 1994;Mani-Ponset et al 1996;Babin et al 1997;Poupard et al 2000). However, the developmental behavior of genes that control the utilization of yolk reserves is virtually unknown (Poupard et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of cellular organelles in the cytoplasmic region in the silver arowana corresponds to those in the larvae of trout, Atlantic halibut (Hippoglossus hippoglossus), sea bass (Dicentrarchus labrax), and pike-perch (Sander lucioperca; Walzer and Schönenberger, 1979a,b;Kjørsvik and Reiersen, 1992;Sire et al, 1994;ManiFig. 3.…”
Section: Discussionmentioning
confidence: 94%
“…Then, the function of the ysl in initiating cell movement becomes less distinct after the completion of gastrulation, and its role in yolk utilization becomes more profound. Most studies thus far dealt with the histochemical aspect of the yolk utilization sequence in teleost development (Vernier and Sire, 1977a,b;Walzer and Schönenberger, 1979a,b;Sire et al, 1994). Poupard et al (2000) described the process of the utilization of yolk reserves during larval development of turbot (Scophthalmus maximus) and emphasized that the apoE gene expression in the yolk cell is parallel to very lowdensity lipoprotein particles exocytosis into a perisyncytial space.…”
mentioning
confidence: 99%
See 1 more Smart Citation